The myth of the sacred : the Charter, the courts and the politics of the constitution in Canada - Abelson, Donald E.; James, Patrick, 1957-; Lusztig, Michael, 1962- (McGill-Queen's University Press, 2002)
A title that challenges the "myth of the sacred" - the idea that certain aspects of the constitutional process - judicial political behaviour, interest group politics, and centralization of power - are untouchable politically.